Characterization and validation of an intra‐fraction motion management system for masked‐based radiosurgery. Issue 5 (4th May 2019) - Knutson, Nels C.; Hawkins, Brad J.; Bollinger, Douglas; Goddu, S. Murty; Kavanaugh, James A.; Santanam, Lakshmi; Mitchell, Timothy J.; Zoberi, Jacqueline E.; Tsien, Christina; Huang, Jiayi; Robinson, Clifford G.; Perkins, Stephanie M.; et al.
Abstract: Purpose: Characterize the intra‐fraction motion management (IFMM) system found on the Gamma Knife Icon (GKI), including spatial accuracy, latency, temporal performance, and overall effect on delivered dose. Methods: A phantom was constructed, consisting of a three‐axis translation mount, a remote motorized flipper, and a thermoplastic sphere surrounding a radiation detector. An infrared marker was placed on the translation mount secured to the flipper. The spatial accuracy of the IFMM was measured via the translation mount in all Cartesian planes. The detector was centered at the radiation focal point. A remote signal was used to move the marker out of the IFMM tolerance and pause the beam. A two‐channel electrometer was used to record the signals from the detector and the flipper when motion was signaled. These signals determined the latency and temporal performance of the GKI. Results: The spatial accuracy of the IFMM was found to be <0.1 mm. The measured latency was <200 ms. The dose difference with five interruptions was <0.5%. Conclusion: This work provides a quantitative characterization of the GKI IFMM system as required by the Nuclear Regulatory Commission. This provides a methodology for GKI users to satisfy these requirements using common laboratory equipment in lieu of a commercial solution.